2023
DOI: 10.1111/imr.13275
|View full text |Cite
|
Sign up to set email alerts
|

Stress/cell death pathways, neuroinflammation, and neuropathic pain

Lu Li,
Tian Li,
Xinyu Qu
et al.

Abstract: SummaryNeuropathic pain is a common and debilitating modality of chronic pain induced by a lesion or disease of the somatosensory nervous system. Albeit the elucidation of numerous pathophysiological mechanisms and the development of potential treatment compounds, safe and reliable therapies of neuropathic pain remain poor. Multiple stress/cell death pathways have been shown to be implicated in neuroinflammation during neuropathic pain. Here, we summarize the current knowledge of stress/cell death pathways and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 150 publications
0
8
0
Order By: Relevance
“…It causes degradation of cytoplasmic proteins and other macromolecules within the lysosome in multicellular organisms [71]. It has been demonstrated to be involved in neuroinflammation and ND, which are characterized by protein aggregation and exacerbated autophagy [72][73][74]. However, the mechanisms involved are not clear [75][76][77].…”
Section: Autophagymentioning
confidence: 99%
“…It causes degradation of cytoplasmic proteins and other macromolecules within the lysosome in multicellular organisms [71]. It has been demonstrated to be involved in neuroinflammation and ND, which are characterized by protein aggregation and exacerbated autophagy [72][73][74]. However, the mechanisms involved are not clear [75][76][77].…”
Section: Autophagymentioning
confidence: 99%
“…Mitochondria also play a crucial role in regulating various forms of cell death, including necroptosis, ferroptosis, and pyroptosis (Bock & Tait 2020). Studies have indicated that neuroimmune mechanisms involved in neuropathic pain may be associated with multiple forms of cell death, such as necroptosis, pyroptosis, and ferroptosis (Bi et L. Li et al 2024). Investigating the role of mitochondrial dysfunction and disul dptosis in neuropathic pain could provide insights for the development of improved therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Cell death is fundamental for the development and homeostasis of organisms 1–3 . Necroptosis is a caspase‐independent modality of programmed cell death (PCD), which was first proposed by Degterev in 2005 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…Cell death is fundamental for the development and homeostasis of organisms. [1][2][3] Necroptosis is a caspase-independent modality of programmed cell death (PCD), which was first proposed by Degterev in 2005. 4,5 Necroptosis can be initiated by death receptors and pathogen receptors, involving clumping dying cells, rupture of cell membrane, swelling of cell bodies and organelles, and inflammasome formation.…”
Section: Introductionmentioning
confidence: 99%